Working Politically: A story of Change about the contribution of research evidence to the new Village Law in Indonesia - and Pellini, Arnaldo; Angelina, Maesy; Purnawati, Endah (Austrialian Community Development and Civil Society Strenghtening Scheme (ACCESS), 2014)
On 18 December 2013, the Indonesian House of Representatives passed the new Village Law, a vote that was the culmination of a journey that had started in 2007. This Story of Change takes the passing of the Village Law as its starting point and describes the relative influence that research-based evidence, produced by the Institute for Research and Empowerment (IRE), has had at critical junctions of the legislative process. This Story of Change concludes that good quality, research-based evidence is necessary but not sufficient to influence policy-making processes. Researchers and research organisations need to think and work politically to achieve their influencing goals and to adapt to changes in local circumstances.